Dene: British Columbia Heritage Series Our Native Peoples Series 1 Volume 9 - British Columbia Division of Curriculum (Author); British Columbia Provincial Museum (Author); British Columbia Provincial Archives (Author) (Queen's Printer, 1952)
The Dene or Athapaskan Indians of British Columbia are only part of a widespread language group. From east to west, the largest continuous habitat of these people extends from the shores of Hudson Bay to the eastern boundary of the Alaska Panhandle. On the north they are found bordering the Arctic Eskimo, and on the south their boundary dips into Coast Salish territory in the neighbourhood of the 51st parallel of latitude. Other groups of the same language stock that became separated in very early times are to be found along the Pacific Coast in Northern California and the State of Washington, and also in the Southwestern United States, where they are known as Navajos and Apaches. Social Studies Bulletin Department of Education Not peer reviewed Historic booklet